Development of Traditional Sports at PORTINA in Temanggung Regency: A Survey Study - Faiz Maulana; Agus Darmawan (Universitas Negeri Semarang, 2025)
This study aims to analyze the development of traditional sports conducted by PORTINA in Temanggung Regency. Using a qualitative descriptive method, data were collected through in-depth interviews with six key informants, direct observation, and documentation. The informants consisted of PORTINA administrators and traditional sports activists actively involved in coaching and promotional activities. The findings indicate that PORTINA Temanggung has implemented a multidimensional development strategy, including school-based integration, community coaching, and digital promotion. Routine training activities are held in public spaces, with a focus on games such as egrang, gobak sodor, and terompah panjang, supported by storytelling and cultural education. The organization also mobilizes local volunteers through training programs and collaborates with schools via extracurricular and cultural events. However, the study also reveals several challenges: limited infrastructure, inadequate funding, and declining youth interest due to modern digital lifestyles. To address these issues, PORTINA adapts by using social media and community-based innovation. The active participation of local communities and contextual coaching approaches are proven effective in sustaining traditional sports. This research contributes to the understanding of traditional sports development in rural areas and highlights the need for multi-stakeholder collaboration and stronger policy support to ensure the sustainability of traditional heritage in contemporary society.